Mutiara De’lagend Tour And Travel / Haslina Hamdan ... [et al.] - Hamdan, Haslina; Rusli, Maisarah; Abdul Rahman, Samsiah; Mat Desa, Mardiana; Yusof, Aina Yuslinda (2002)
The business plan is prepared for the company that builds under the company act. Our company or business named is Mutiara De’lagend Tour And Travel which there are five shareholders. Our main operation is almost providing tour package, jetty tranfer, and coach transfer, sightseeing tour and car rental for those who are interested.